Hyperinsulinemia Can Cause Kidney Disease in the IGT Stage of OLETF Rats via the INS/IRS-1/PI3-K/Akt Signaling Pathway - Yi Zhang; Shaohua Yang; Xiao Cui; Juhong Yang; Miaoyan Zheng; Junya Jia; Fei Han; Xiaoyun Yang; Jingyu Wang; Zhenhong Guo; Bai Chang; Baocheng Chang (Journal of Diabetes Research)
Aims. We investigated the changes of renal structure and its function in normal glucose tolerance (NGT), impaired glucose tolerance (IGT), diabetes mellitus (DM), and diabetic kidney disease (DKD) stages in OLETF rats and explored the role of the INS/IRS-1/PI3-K/Akt signaling pathway. Methods. OLETF rats were assigned into four groups on the basis of OGTT results and 24 h urinary microalbumin: NGT, IGT, DM, and DKD groups. The changes of renal structure and function and the corresponding pathological changes were observed. The absorption of albumin and the expression of megalin, cubilin, IRS-1, PI3-K, and Akt in NRK-52E cells were measured after being stimulated by different concentrations of insulin. Results. In the IGT group, the index which reflects the function of renal tubule-like N-acetyl-β-glucosaminidase, neutrophil gelatinase-associated lipocalin, retinol-binding protein, and cystatin C was higher than those in the control group and the NGT group (P<0.05). Significant renal structure damages, especially in renal tubules, were observed in the IGT group. In the presence of insulin at a high concentration, the IRS-1/PI3-K/Akt signaling pathway in renal tubular epithelial cells was inhibited, and the expression of megalin and cubilin was significantly downregulated which was accompanied by a minimum uptake of albumin. Conclusions. In contrast to DKD, the renal structural damage and functional changes in the IGT stage, in which we propose the term “IGT kidney disease,” mainly manifest as renal tubular injury. Insulin resistance and compensatory hyperinsulinemia may be involved in its pathogenesis.